1989
DOI: 10.1111/j.1945-5100.1989.tb00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible relationship between the Farmington meteorite and a seismically detected swarm of meteoroids impacting the Moon

Abstract: Abstract— The Farmington ordinary L5 chondrite with its uniquely short cosmic‐ray exposure age of less than 25 000 years may have been a member of a large meteoroid swarm which was detected by the Apollo seismic network when it encountered the Moon in June 1975. The association implies that the parent body of the Farmington meteorite was in an Earth‐crossing orbit at the time the swarm was formed. This supports the idea that at least some meteorites are derived from the observable population of Earth‐crossing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…This author also suggested that Seres may have been in a pre-terrestrial orbit very close to the Sun, which caused a late heating event to several hundred°C, in order to explain the metallographic texture and depletion of cosmogenic noble gases. A similar conclusion has been postulated for Farmington to explain its very young CRE age (e.g., Heymann et al, 1967;Oberst, 1989). Our constraints for a very young CRE age <0.5 Ma imply LAP 031047 was shielded from galactic cosmic rays before $0.5 Ma, possibly because its location was >1-2 m from the surface of its parent asteroid (e.g., Eugster, 2003;Leya and Masarik, 2009) or it was reheated in the last 0.5 Ma.…”
Section: Noble Gas Inferencessupporting
confidence: 61%
“…This author also suggested that Seres may have been in a pre-terrestrial orbit very close to the Sun, which caused a late heating event to several hundred°C, in order to explain the metallographic texture and depletion of cosmogenic noble gases. A similar conclusion has been postulated for Farmington to explain its very young CRE age (e.g., Heymann et al, 1967;Oberst, 1989). Our constraints for a very young CRE age <0.5 Ma imply LAP 031047 was shielded from galactic cosmic rays before $0.5 Ma, possibly because its location was >1-2 m from the surface of its parent asteroid (e.g., Eugster, 2003;Leya and Masarik, 2009) or it was reheated in the last 0.5 Ma.…”
Section: Noble Gas Inferencessupporting
confidence: 61%
“…The best direct evidence of a meteorite stream is Halliday's (1987) photographic observations of two meteors, one of which yielded an LL chondrite fall, from the same orbit. Other authors, on less certain evidence, have suggested that there may be streams of H chondrites (Wood, 1982;Dodd, 1992;Wolf and Lipschutz, 1992), L chondrites (Wood and Silliman, 1983;Oberst, 1989) and SNC achondrites (Treiman, 1992). Meteorite falls may also occur in clusters, falls in rapid succession without common or similar fall days.…”
Section: Introductionmentioning
confidence: 99%
“…Meteorite falls may also occur in clusters, falls in rapid succession without common or similar fall days. Clusters of meteoroid impacts have been recognized in data from the Apollo lunar seismic network (Oberst andNakamura, 1987, 1991), although it is possible that these meteoroids are unrelated to the meteorites that fallon Earth.…”
Section: Introductionmentioning
confidence: 99%